Implementasi Metode Topsis Pada Aplikasi Penilaian Karyawan Pada Enspire Studio - Maynacky; Hariyanto, Ribfan; Agung, Halim (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
In this era of globalization, the competition companies in an industry increasingly tight. Companies are expected to provide the best service to consumers and its business partners. This causes the human resources required for showing the best performance with the company was thus able to compete with its competitors. And therefore the assessment of the most important elements are the employees of a company which could reflect how a company has the HR (human resources) are good or not, because Human Resource are a very important factor in a companies or institutions for the sake of the progress of the company. In this Research of the assessment application the method that we were using is TOPSIS algorithm (Technique for Order of Preference by Similarity to Ideal Solution) which aims to test whether the TOPSIS method implemented directly in the application of assessment into employees. Based on data for 10 months, as we can see the data of the final value in the table data to the actual assessment of the employee, and then compare the test results can be viewed by using the application shows the results of the final value is the same as the actual data the difference is only in decimal, based on the test so we can conclude that the success percentage rate method is 80%. Hence the conclusion that can be drawn from the results of testing on TOPSIS method in the use of application implementations, we can use this method and applied this because the success rate is quite high. So that it can be used as a consideration for the final decision by the directiors.